Intrapatient emergence of OXA‐247: a novel carbapenemase found in a patient previously infected with OXA‐163‐producing Klebsiella pneumoniae. (12th February 2013) - Gomez, S.; Pasteran, F.; Faccone, D.; Bettiol, M.; Veliz, O.; De, D.; Rapoport, M.; Gatti, B.; Petroni, A.; Corso, A.; Cantón, R.
Abstract Two genetically related Klebsiella pneumoniae strains carrying OXA‐type carbapenemases were isolated from a single patient 1 month apart. Kpn163 harboured OXA‐163 and Kpn247 a new variant named OXA‐247 that showed susceptibility to carbapenems and expanded‐spectrum cephalosporins similar to OXA‐48. Our epidemiological, biochemical and molecular results suggest the intrapatient emergence of blaOXA‐247 from blaOXA‐163.